ANALISIS TINGKAT PENGETAHUAN LINGKUNGAN DENGAN SIKAP PEDULI LINGKUNGAN SISWA SMA 3 MAJENE PROVINSI SULAWESI BARAT - Dirawan, Gufran Darma (Pascasarjana Universitas Negeri Makassar, 2023)
This study aims to look at the relationship and the significance of the contribution at the level of knowledge with an attitude of caring for the environment for students at SMA Negeri 3 Majene. This research was conducted on all students of class X consisting of 5 classes, with a total population of 180 people and a sample of 130 students. This type of research is a descriptive study that describes various data using correlation techniques. Random sampling was carried out in collecting sample data and using tests for environmental knowledge and questionnaires for environmental attitudes supported by observation sheets and interview guide sheets. The results showed that the correlation value formed from the level of students' environmental knowledge with students' environmental care attitude was 0.327 (low) with a contribution of 10.7% and the regression analysis showed the regression equation Ŷ = 81.557 + 0.157 X. From the calculation results obtained t count 3.915 > t table 1.9978. This indicates that Ha is accepted and H0 is rejected, so it can be concluded that there is a significant relationship between the level of environmental knowledge and the environmental care attitude of students at SMA Negeri 3 Majene.